(untitled) (Heritage, 2021)
The need to unite capital in order to meet the needs of primarily its own shareholders caused tne establishment of a large number of monetary institutes in the Kingdom of Serbia. These financial institutions were not divided into commercial banks and purely banking institutions. so money institutions often appered as owners of various industrial and commercial companies. With the end of the Great War on the territory of Serbia, ther was a great need for reconstruction and construction, so thar the shortage of capital was chronic. In such circumastances, during 1922, the Industrial and Commercial Bank of Niš was founded, with at thet time, a modest million dinars of share capital. The composition of the shareholders directed the business policy of this bank, so that at first, in addition to banking, it also dealt with commodity affairs. However, the bank’s management quickly realized thet working with short-term bill loans was the most profitable and this type of business became not only central bur also the only one. By the end of 1924, the bank’s capital was increased to two million dinars, and the success of its business was feflected in the fact that until the outbreak of the banking crises in Yugoslavia in 1931, this mometary institution regularly paid dividends to its shareholders. The severe economic crisis in Yugoslavia duging the 1930s almost completely paralyzed the work of banks, and many stopped working. Industrial and Commercial Bank of Niš a financially stable institution and at no time was its business questioned. This institution managed to provide earnings to its shareholders even in such circumstances. The reasons for htat can be found in the structure of Niš and did not put pressure on the new institution regarding the withdrawal of savings deposits. The industrial and Commercial Bank was menaged by the Cvetković, Miljković and Pešić families, who owned almost 90% of the shares of this institution. The outbreak of the World Wor Two in the territory of the Kingdom of Yugoslavia hindered the further work of the Industrial and Commercial Bank, while the govermnment established in Yugoslavia after the 1945 elections shut down all private institutions, which made this institution cease to exist.